Identification of Students’ Misconceptions in Functions Topic - Gunawan, Rilla Gina; Maulana, Yuniza; Putri, Rahmi (Indonesian Journal of Science and Mathematics Education, 2021)
This study aimed to identify students' misconceptions on the topic of function. The research used is qualitative research using a descriptive approach. The subjects of this study were class X MIA3 selected by using purple sampling and snowball techniques. The research instrument was a written test using diagnostic test techniques for misconceptions, interviews, and observations. The qualitative data analysis techniques in this research are data reduction, data presentation, and conclusion drawing/verification. Based on the research, there are 4 students who experience misconceptions in class X MIA3 on the topic of the functions. Out of 6 indicators of misconceptions, the reasons were caused by a lack of student interest in learning, underestimating the concept of functions so that they think learning the concept of functions is very easy, embarrassed to ask questions when studying, and never repeat lessons at home so that students cannot answer questions given by the teacher.